Judicial Independence and Human Rights in Latin America - Skaar, E. author. aut Link
XVII, 297 p.
Keywords: This comparative analysis, focusing on Argentina, Chile, and Uruguay, explores the complex relationship between executive politics and judicial action, showing that judicial independence is a crucial factor in prosecution. It will engage Latin Americanists as well as all who are concerned with justice and human rights around the world.